Elevated Lipoprotein(a) as a potential residual risk factor associated with lipid-rich coronary atheroma in patients with type 2 diabetes and coronary artery disease on statin treatment: Insights from the REASSURE-NIRS registry. (May 2022) - Nakamura, Hayato; Kataoka, Yu; Nicholls, Stephen J.; Puri, Rishi; Kitahara, Satoshi; Murai, Kota; Sawada, Kenichiro; Matama, Hideo; Iwai, Takamasa; Honda, Satoshi; Fujino, Masashi; Takagi, Kensuke; et al.
Abstract: Background and aims: The residual risk of atherosclerotic cardiovascular disease (ASCVD) in patients with diabetes on statin therapy warrants identification of other pro-atherogenic drivers. Lipoprotein(a) [Lp(a)] promotes the formation of necrotic cores within vessel walls. Given that patients with diabetes have an Lp(a)-associated ASCVD risk, Lp(a) might lead to plaque vulnerability in patients with diabetes on statin therapy. Methods: We analyzed target lesions that underwent PCI in 312 patients with coronary artery disease (CAD) on statin treatment from the REASSURE-NIRS registry (NCT04864171). Maximum 4-mm lipid-core-burden index (maxLCBI4mm ) in target lesions was measured with near-infrared spectroscopy (NIRS) imaging. The relationship between Lp(a) levels and maxLCBI4mm was investigated in patients with and without diabetes. Results: High-intensity statin use ( p = 0.49) and on-treatment low-density lipoprotein cholesterol (LDL-C) ( p = 0.32) and Lp(a) levels ( p = 0.09) were comparable between patients with and without diabetes. Lp(a) levels were significantly associated with maxLCBI4mm in patients with diabetes ( p = 0.01) but not in patients without diabetes ( p = 0.96). Multivariate analysis showed that LDL-C levels ( p = 0.03) predict maxLCBI4mm in patients without diabetes, but not Lp(a) levels ( p = 0.91). Both LDL-C ( p = 0.01) and Lp(a) ( p = 0.04) levels were independent predictors of maxLCBI4mm in patients with diabetes. Even in patients with diabetes achieving LDL-C <1.8 mmol/L (70 mg/dL), Lp(a) levels remained associated with maxLCBI4mm ( p = 0.04). Conclusions: A significant relationship between Lp(a) and maxLCBI4mm exists in patients with diabetes and CAD on statin treatment, even with LDL-C <1.8 mmol/L (70 mg/dL). Lp(a) might be associated with more vulnerable coronary atheroma in patients with diabetes despite receiving statin therapy. Graphical abstract: Image 1 Highlights: We analyzed the association of Lp(a) levels with near-infrared spectroscopy (NIRS)-derived Maximum 4-mm lipid-core-burden index (maxLCBI4mm ) in statin-treated coronary artery disease (CAD) patients. Lp(a) level was significantly associated with maxLCBI4mm in patients with diabetes but not in patients without diabetes. Even in patients with diabetes and on-treatment LDL-C <1.8 mmol/L, Lp(a) still predicted high maxLCBI4mm . These findings indicate Lp(a) as a contributor to lipid-rich plaque formation in CAD patients with diabetes receiving a statin.